2004
DOI: 10.1191/1358863x04vm571oa
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal monocyte recruitment and collateral artery formation in monocyte chemoattractant protein-1 deficient mice

Abstract: Monocyte chemoattractant protein 1 (MCP-1) has been shown to be effective for the stimulation of collateral artery formation in small and large animal models. The availability of a genetic knockout mouse enables evaluation of the importance of the role of MCP-1 in the natural course of collateral artery growth. In a total of 21 MCP-1 À=À as well as 13 of the appropriate genetic background controls (f129Sv=J X C57Bl=6JgF1), a femoral artery ligation was performed. Subsequently, a polyethylene catheter, connecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 24 publications
3
43
0
Order By: Relevance
“…7 Correspondingly, infusion of this chemokine into the proximal stump of an occluded femoral artery in rabbits markedly enhanced arteriogenesis, 25 whereas this was diminished in MCP-1 or CC chemokine receptor 2-deficient mice. 26,27 Despite its importance for the initiation of arteriogenesis, only little is known about the mechanisms that control the expression of MCP-1 in this context. Therefore, we subjected small second order branches of the mouse mesenteric artery to proarteriogenic flow conditions and identified the SMCs of the media as the main source of MCP-1.…”
Section: Discussionmentioning
confidence: 99%
“…7 Correspondingly, infusion of this chemokine into the proximal stump of an occluded femoral artery in rabbits markedly enhanced arteriogenesis, 25 whereas this was diminished in MCP-1 or CC chemokine receptor 2-deficient mice. 26,27 Despite its importance for the initiation of arteriogenesis, only little is known about the mechanisms that control the expression of MCP-1 in this context. Therefore, we subjected small second order branches of the mouse mesenteric artery to proarteriogenic flow conditions and identified the SMCs of the media as the main source of MCP-1.…”
Section: Discussionmentioning
confidence: 99%
“…28 -32 Conversely, animals deficient in MCP-1 or CCR2-chemokine receptor, an MCP-1 receptor, have been shown to display reduced monocyte/macrophage infiltration and collateral formation. 33,34 Previous work has indicated that OPN is an important mediator of macrophage adhesion and migration, and other studies have shown that OPN may be critical for macrophage infiltration into sites of injury in vivo. 15 In addition, two recent reports have indicated that OPN plays a key role in the regulation of the hematopoietic stem cell (HSC) niche in bone marrow.…”
Section: Duvall Et Al Osteopontin In Hind Limb Ischemia 293mentioning
confidence: 99%
“…9,30 Genetically modified mice deficient for either MCP-1 or CCR2 have an impaired monocyte response and less recovery of perfusion after interruption of arterial inflow. 12,13 In this study, the molecular signal for monocyte ␣ 5 -integrin at 4 days was markedly reduced in MCP-1 Ϫ/Ϫ mice compared with wild-type mice. The relatively mild differences in blood flow in the 2 groups was likely due to the early time interval (4 days).…”
Section: Discussionmentioning
confidence: 87%
“…Greater differences in flow would be expected at 7 to 21 days. 12,13 Interactions between VCAM-1 on the endothelium and integrins such as VLA-4 (␣ 4␤1 ) contribute to slow rolling and firm adhesion of monocytes and lymphocytes in the microcirculation. Targeted CEU in ischemic limbs detected VCAM-1 expression on the microvascular endothelium in a temporal pattern that paralleled monocyte ␣ 5 -integrin signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation